Comparative study of the efficacy of fusidic acid and povidone iodine in childhood impetigo - Szepetiuk, Gregory; Henry, Frédérique; Piérard, Gérald E. (Journal of Pediatric Infectious Diseases, 2006)
Impetigo is a superficial bacterial infection of the skin. It is a contagious condition particularly affecting children. In many instances, a topical antibacterial treatment is recommended to clear the disease. Topical antibiotics and antiseptics can be used, but the risk for antibiotic-induced bacterial resistance of the community-acquired type has been pointed out. The present study was undertaken as a randomized intra individual comparative trial between fusidic acid (FA) cream and povidone iodine (PVP-I) gel in 40 children suffering from impetigo. Cultures revealed Staphylococcus aureus in the vast majority of the cases. The lesions present on each upper limb were treated twice daily with one or the other test formulation. Clinical assessments were performed twice weekly until cure. After one week, cure was obtained in 57.5% of the PVP-I-treated limbs compared to 32.5% of the FA-treated limbs. At the end of treatment cure was obtained first on the PVP-I treated sites in 67.5% of cases compared to 15% on the FA-treated sites. Clinical cure occurred simultaneously on both test sites in 17.5% of cases. In conclusion, PVP-I provided faster clinical cure than FA. Considering the treatment cost, the rising community-acquired staphylococci resistance to FA, and the results of the present study, PVP-I gel appears superior to FA cream in childhood impetigo.
Keywords: Antiseptic; antibiotic; impetigo; fusidic acid; povidone iodine